A Novel Intronic Mutation Reduces HAX1 Level and is Associated With Severe Congenital Neutropenia. Issue 1 (January 2022) - Goktas, Serdar; Azizoglu, Zehra B.; Petersheim, Daniel; Erdogan, Merve; Eke Gungor, Hatice; Bisgin, Atil; Tuğ Bozdoğan, Sevcan; Eken, Ahmet; Unal, Ekrem; Klein, Christoph; Patiroglu, Turkan
Abstract : Severe congenital neutropenia (SCN) is a rare disease. Autosomal recessive forms of SCN are more frequent in countries where consanguineous marriages are common. In this report, we describe a 54-day-old female with neutropenia who presented with ecthyma gangrenosum. Clinical exome sequencing was used to identify the mutation. HAX1 messenger RNA and isoforms were examined by real-time quantitative and conventional polymerase chain reaction. Bone marrow aspiration was stained by hematoxylin and eosin. Granulocytes were tested for apoptosis upon H2 O2 exposure. T-cell proliferation was tested by flow cytometry. Clinical exome sequencing revealed a novel homozygous acceptor splice site mutation in intron 3 of HAX1 (c.505-1G>C), which reduced both isoforms A and B of HAX1 messenger RNA. The Western blot studies showed a complete absence of HAX1 protein. The purified neutrophils from the patient showed increased apoptosis upon H2 O2 exposure, whereas T-cell proliferative responses to various stimuli were intact. The patient was treated with combined antibiotics, filgrastim, and placed on antibiotics prophylaxis. To the best of our knowledge, our data provide the first experimental evidence for HAX1 deficiency because of a splice site mutation. Although 3 other splice site variants have been deposited in databases, functional studies were missing. This novel variant of HAX1 may explain the SCN and secondary infections in our patients. Abstract : Supplemental Digital Content is available in the text.